OPTIMIZATION OF ACCESS POINT ARRANGEMENT AND PLACEMENT IN THE INDOOR ROOM OF SMP NEGERI 6 SALATIGA USING GENETIC ALGORITHM - Arzan Khoirul Anam; Wiwin Sulistyo (Jurnal Teknik Informatika (Jutif), 2022)
Access points are generally only recommended to load up to 40 clients only. Thus, proper placement and arrangement of access points in a room or building can optimize the signal strength received by users. The purpose of this study is to optimize the arrangement and placement of access points built using the genetic algorithm method. In the system built, the user is required to input the number of populations, iterations and the number of nodes 1 and 2. In the program implementation, the population functions to load the genes resulting from the possible placement of the access point based on the iteration results. The access point placement optimization system using the genetic algorithm method has been successfully implemented, the system can perform calculations in processing the ideal access point placement. Access point placement using genetic algorithms can provide recommendations for network architecture design in terms of the coverage area that needs to be used so that designers can save time on node point design and estimate the ideal price in determining the number of access points for network installation and can assist in determining the required coverage area. ideal for schools.